Optimalisasi Fungsi Keluarga dalam Rangka Membentuk Generasi Berkualitas di Pulau Tegal Kec. Padang Cermin Kabupaten Pesawaran, Lampung. - Dewie Brima Atika; Nana Mulyana; Yulianto Yulianto; Dian Kagungan (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
This service aims to increase participants' knowledge about family functions, and increase understanding of children's rights. Optimization of family functions is an important factor for the future development of the child's personality. One of them is instilling moral and religious values in children from an early age. By giving and instilling moral and religious values from an early age, it is hoped that children will be able to distinguish between good and bad actions, right and wrong so that they can be applied to children's daily lives. So that a generation that is physically and mentally healthy is formed, as one of the main assets for the sustainability of Indonesia's development. The PKM method consists of three stages: a) Situation analysis is carried out through research tracing and studies of related themes; b) Object intervention through lectures, focus group discussions, and mentoring for two months. The target of this PKM activity is mothers on Tegal Island, Pesawaran Regency.